Bioorganometallic Chemistry - Apfel, Ulf-Peter; Weigand, Wolfgang (De Gruyter Textbook, 2020)
Bioorganometallic Chemistry is an excellent introduction to this transdisciplinary field which is straddled with biochemistry, medicine and organometallic chemistry. The book is a comprehensive review on the latest advances of this rapidly growing area, as well as historical background and future trends, revealing a tremendous potential of bioorganometallic compounds as novel drug candidates and diagnostic tools.